6‐Methyl 3‐chromonyl 2, 4‐thiazolidinedione/2, 4‐imidazolidinedione/2‐thioxo‐imidazolidine‐4‐one compounds: novel scavengers of reactive oxygen species. (11th July 2013) - Berczyński, Paweł; Duchnik, Ewa; Kruk, Irena; Piechowska, Teresa; Aboul‐Enein, Hassan Y.; Bozdağ‐Dündar, Oya; Ceylan‐Unlusoy, Meltem
ABSTRACT The benefits of antioxidants on human health are usually ascribed to their potential ability to remove reactive oxygen species providing protection against oxidative stress. In this paper the free radicals scavenging activities of nine 6‐methyl 3‐chromonyl derivatives (CMs) were evaluated for the first time by the chemiluminescence, electron paramagnetic resonance, spin trapping and 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH) methods. The total antioxidant capacity was also measured using a ferric‐ferrozine reagent. Compounds having a hydrogen atom at the N3‐position of the β‐ring were effective in quenching CL resulted from the KO2/18‐crown‐6‐ether system (a source of superoxide anion radical, <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg5nnzgmwr" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />O2¯</alternatives>) in a dose‐dependent manner over the range of 0.05–1 mmol/L [IC50 ranged from 0.353 (0.04) to 0.668 (0.05) mmol/L]. The examined compounds exhibited a significant scavenging effect towards hydroxyl radicals (HOHO), produced by the Fenton reaction, and this ranged from 24.0% to 61.0%, at the concentration of 2.5 mmol/L. Furthermore, the compounds examined were also found to inhibit DPPH and this ranged from 51.9% to 97.4% at the same concentration. In addition, the use of the total antioxidant capacity assay confirmed that CM compounds are able to act as reductants. According to the present study, CM compounds showed effective in vitro free radical scavenging activity and may be considered as potential therapeutics to control diseases of oxidative stress‐related etiology. Copyright © 2013 John Wiley & Sons, Ltd.